An Empirical Study of the Dimensionality of the Mathematical Knowledge for Teaching Construct. (November 2019) - Copur-Gencturk, Yasemin; Tolar, Tammy; Jacobson, Erik; Fan, Weihua
This study explores the dimensionality of mathematical knowledge needed by elementary school teachers. Specifically, we focus on the construct of Mathematical Knowledge for Teaching to investigate whether common mathematical content knowledge (the generic mathematical knowledge that is held by an educated adult), specialized content knowledge (the content knowledge that is unique to teaching), and pedagogical content knowledge (knowledge of the content, students, and teaching) can be distinguished empirically. Findings from a secondary analysis of data collected from upper elementary teachers in the Measures of Effective Teaching project ( N = 397) suggest the most parsimonious explanation of Mathematical Knowledge for Teaching construct is that it is unidimensional. We argue, based on the findings and limitations we identified, that researchers should reconsider both the structure of the components that make up the content knowledge for teaching and the effects of item design on the dimensionality of the construct.